Análisis de un test específico de proyecciones en la lucha libre masculina - Matos Pérez, Z.; Rios Hernández, A. N.; Nicot Balón, R. G.; Valdés Izaci, E. (Revista Cubana de medicina del deporte y la cultura fisica, 2019)
An descriptive retrospective study was conducted in an universe of 28 male athletes belonging to the national team of wrestling from Cuba. The sample was the 10 elite athletes prioritized. In recent years there are numerous sports that have undergone regulatory changes. The wrestling has turned out to be one of these, what has contributed to that the demands are greater and the methods of control of the fighters are modified. A new specific test developed by Ríos and Valdés, was applied in order to determine the behavior of pedagogical and biomedical variables through the modifications present in two moments of the macrocycle (2013-2014), in the general and competitive preparation. The statistical processing for the comparison among moments wasperformed by the non-parametric Wilcoxon test for two related samples. The Kruskall-Wallis nonparametric test was used for the comparison among weight categories with more than two independent samples. This study evidencesthat there was improvement in the effectiveness of the techniques performed by the athlete in the second test with respect to the first, concluding that there was an increase in the technical-tactical domain on the part of the fighters, as well as the increase in the number of techniques with lactate and heart rate figures, which yield values that correspond to an adequate biological adaptation, as a consequence of the training loads received by the national team's fight practitioners.